Sustitución parcial de harina de trigo (Triticum aestivum L) por harina de frejol (Phaseolus vulgaris L) y su incidencia en las características físico-químicas microbiológicas y sensoriales en la elaboración de extruídos tipo snack - García Mesías, Grace Kazandra (2023)
Extrusion processes cause changes in the physicochemical parameters and the quality of cereal-based products, in addition, snacks are known as snacks that do not contribute nutritionally, and are characterized by high salt and fat content. In this sense, the main objective of this research is to perform a partial substitution of wheat flour (Triticum aestivum L) for bean flour (Phaseolus vulgaris L) and its impact on the physicochemical, microbiological and sensory characteristics in the preparation of extruded snack-type products. First, the raw material was characterized, where protein and ash presented high values in raw bean flour, while in moisture and fiber the most representative values were in cooked bean flour, these results were compared with the INEN 616 standard, which is within the range to be classified as good quality raw material, then wheat flour was replaced by bean flour, resulting in T5 as the best treatment, consisting of 60% wheat flour + 60% cooked bean flour. The physical-chemical analysis of the final product showed a moisture content of 2.62%, peroxide 0.00 MeqO2/kg, and comparing these results with INEN 256, it was determined that it is within the requirements of the standard; likewise, the microbiological analysis showed values <10 CFU/g, making it a safe product for human consumption. By means of the sensory analysis in the acceptability attribute, T5 was identified as the best treatment. Finally, the nutritional characterization of the product was carried out.